The response to disability in higher education: an analysis of programs and services for people with disabilities: the case of the University of La Laguna - Márquez-González, Laura María; Martínez-Murciano, María Carmen; Olmos-Raya, Elena; Pérez-Jorge, David (Frontiers in Education, 2025)
IntroductionThis study analyses the perceptions of students with disabilities and their lecturers at the University of La Laguna (ULL), focusing on the inclusion strategies implemented and their effectiveness in promoting educational equity.MethodsA mixed-methods design was employed, combining quantitative and qualitative approaches. Data were collected from 115 participants — 36 students with disabilities and 79 lecturers, between 2016 and 2018. Structured questionnaires and interviews were administered. Quantitative data were analysed using SPSS software, while qualitative data were examined through thematic content analysis.ResultsThe findings highlight the importance of fostering close collaboration among students, teaching staff, and the Programme for Students with Specific Support Needs (PAED). Key challenges identified include physical and communicative accessibility barriers, as well as a lack of training in addressing student diversity. Moreover, the absence of an inclusive institutional culture, as embedded within ULL’s policies and practices, was noted.DiscussionThe study highlights the urgent need to enhance inclusion strategies, particularly by improving accessibility and providing targeted training for academic and technical staff. Enhancing coordination between PAED, lecturers, and students is essential to creating a genuinely inclusive university environment. Despite limitations related to the sample size, the findings offer valuable insights for improving the institutional response to the diverse student population entering higher education.